2021
DOI: 10.1016/j.jcot.2021.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of leucocyte poor vs leucocyte rich platelet-rich plasma in the management of lateral epicondylitis: Systematic review & meta-analysis of randomised controlled trials

Abstract: Study design: Systematic Review & Meta-analysis. Objectives: We aim to comparatively analyse the efficacy and safety of using leucocyte-poor platelet rich plasma (LP-PRP) against leucocyte-rich platelet rich plasma (LR-PRP) in the management of lateral epicondylitis. Materials and methods: We conducted independent and duplicate electronic database searches including PubMed, Embase, Web of Science and Cochrane Library till September 2020 for randomised controlled trials analyzing the efficacy and safety of LP-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Although leukocytes play a key role in tissue repair and provide ideal protection against infectious factors, their pro-inflammatory and immune effects can also cause adverse local reactions, which will weaken the role of platelets, that is, low leukocyte PRP has greater benefits. 25 - 27 Therefore, the centrifugal conditions for the preparation of PRP need to be optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Although leukocytes play a key role in tissue repair and provide ideal protection against infectious factors, their pro-inflammatory and immune effects can also cause adverse local reactions, which will weaken the role of platelets, that is, low leukocyte PRP has greater benefits. 25 - 27 Therefore, the centrifugal conditions for the preparation of PRP need to be optimized.…”
Section: Resultsmentioning
confidence: 99%
“…The use of preparations with a low content of platelets can be confusing and could be the reason for inconclusive results of systemic reviews and meta-analyses. On the other hand, research increasingly shows that there is no significant difference in the clinical effect between the different types of PRP [15]; therefore, it cannot be ruled out with certainty that the injection technique itself is of great importance in achieving clinical improvement [48]. Due to the lack of comparison with the control group, it cannot be excluded for sure, that the positive results of the PRP treatment in our study were related to the injection technique itself, a placebo-effect or to the recommended post-treatment rehabilitation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…There are many doubts about the efficacy of PRP injection in lateral elbow tendinopathy. Most publications have presented significant improvements, being better than corticosteroid injection at more than three months after treatment or even being equal to surgery [13][14][15][16]. On the other hand, some studies have reported similarly good outcomes after saline or autologous blood injection [14,17] while three months appeared to be the cut-off point for positive PRP treatment results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even some studies have shown a catabolic gene expression in leucocyte-rich PRP relating to impaired tissue healing in in-vitro studies. 15,16 However, various randomized controlled trials and meta-analyses of studies 17,18 that analyzed this variable did not nd any clinical difference in either of the groups.…”
Section: Introductionmentioning
confidence: 98%